RELEVANCE OF RAPID IMMUNODIAGNOSTIC TEST KITS IN MALARIA DIAGNOSIS - AYOOLA, SAHEED A.; ADEWUMI, SEGUN S.; OYEDELE, JULIUS O.; SAIDU, ADAMU B.; MUSTAPHA, KHAFAYAT O.; ADETORO, OLUWAKEMI B.; TIWARI, RAM P. (International Journal of Current Pharmaceutical Research, 2015)
Over the past few decades, rapid immunodiagnostic test kits (RIDTK) have been used to compliment microscopy in parasitemia detection. In order to reduce malaria mortality in Sub-Saharan Africa where malaria is endemic, the most important characteristics required for a diagnostic method are high sensitivity for detecting Plasmodium falciparum and rapid availability of test results. However, in environments where malaria incidence is low, high specificity and high sensitivity for detection of non-P. falciparum species is very important; a repeat testing paradigm is also highly necessary. The requirements of a malaria rapid immunodiagnostic test differ with respect to regional malaria epidemiology and the goals of a malaria control program. Prompt and accurate diagnosis is very important for proper management and prevention of malaria and also to prevent morbidity, mortality and indiscriminate use of anti malaria agents. There has been a great progress in the development of many rapid and specific immunodiagnostic tests for diagnosing patients suffering from malaria. In this regard, the development is done with respect to the antigen(s) the antibodies are meant to detect. The three categories of rapid immunodiagnostic test kits that have so far been developed comprise Histidine-Rich Protein 2 (HRP-2), Parasite specific plasmodium lactate dehydrogenase (pLDH) and aldolase. Despite the fact that microscopy is still used as the reference test for malaria detection and having the ability to detect lower parasite densities, there abound a lot of shortcomings with it. However, the advent and development of rapid immunodiagnostic test kits has brought lasting solutions to some of these problems In order to reduce morbidity, mortality and transmission of malaria, prompt diagnosis and adequate treatment is highly essential and these can be achieved if an only when malaria rapid immunodiagnostic tests are used.